Does disability modify the relationship between labour force status and psychological distress among young people?. (10th December 2020) - Shields, Marissa; Dimov, Stefanie; King, Tania L; Milner, Allison; Kavanagh, Anne; Spittal, Matthew J; Disney, George
Abstract : Objective: To examine the association between labour force status, including young people who were unemployed and having problems looking for work, and psychological distress one year later. We then assessed whether this association is modified by disability status. Methods: We used three waves of cohort data from the Longitudinal Surveys of Australian Youth. We fitted logistic regression models to account for confounders of the relationship between labour force status (employed, not in the labour force, unemployed and having problems looking for work) at age 21 years and psychological distress at age 22 years. We then estimated whether this association was modified by disability status at age 21 years. Results: Being unemployed and having problems looking for work at age 21 years was associated with odds of psychological distress that were 2.48 (95% CI 1.95 to 3.14) times higher than employment. There was little evidence for additive effect measure modification of this association by disability status (2.52, 95% CI −1.21 to 6.25). Conclusions: Young people who were unemployed and having problems looking for work had increased odds of poor mental health. Interventions should focus on addressing the difficulties young people report when looking for work, with a particular focus on supporting those young people facing additional barriers to employment such as young people with disabilities.